Assessment of Adult ADHD in Clinical Practice: Four Letters—40 Opinions. Issue 9 (July 2023) - Schneider, Brooke C.; Schöttle, Daniel; Hottenrott, Birgit; Gallinat, Jürgen; Moritz, Steffen
Objective: Despite guidelines providing detailed recommendations for the assessment of ADHD in adults and increasing clinician awareness of the persistence of ADHD into adulthood, ADHD remains under diagnosed in many countries.Method: A survey of 178 clinicians who regularly perform assessments for adult ADHD was conducted between February 2015 and 2016 to identify possible causes of underdiagnosis related to assessment practices.Results: There was a lack of consensus among clinicians regarding which symptoms are relevant to adult ADHD. Only "difficulties concentrating" was endorsed as a core feature of adult ADHD by a majority of respondents. Few clinicians used (semi-)structured interviews. Psychologists were less likely than physicians to recommend medication.Conclusion: Further clinician training on core symptoms of adult ADHD and diagnostic practices congruent with guideline recommendations may improve symptom recognition among clinicians and diagnostic accuracy. Identification of barriers to the implementation of diagnostic practices recommended by guidelines is needed.